Synthesis of 4-oxo-2,5-cyclopentadiene Using Multi-component Reactions of Primary Amines and Electron Deficient Acetylenic Compounds with Triphenylphosphine in Water - Seyfi, Samereh; Rostami-Charati, Faramarz; Hossaini, Zinatossadat; R. Zardoost, Mohammad (Letters in Organic Chemistry, 2014)
A water-accelerated multicomponent synthesis of organic target molecules has been used as a key method for the preparation of cyclopentadiene derivatives. The three-component condensation reactions of primary amines with alkyl propiolates in the presence of triphenylphosphine in water at 80 °C are developed as efficient and clean green synthetic procedures for the high-yielding preparation of 4-oxo-2,5-cyclopentadiene-1,2-dicarboxylate derivatives.
Keywords: multi-component reaction